Hijmania, a replacement name for Maria (Moraceae) - Vianna Filho, Marcelo Dias Machado; Maia, Vitor Hugo; Mansano, Vidal De Freitas; Da Costa, Andrea Ferreira (Phytotaxa, 2016)
The genus Maria Vianna was proposed by Vianna et al. (2013: 290) for a small group of the tribe Dorstenieae (Moraceae), components of the undergrowth in the rainforests of tropical Africa. However, as the authors chose a later homonym, Maria M.D.M.Vianna is an illegitimate name (Art. 53.1 of the ICN, McNeill et al. 2012). This was discovered after checking the nomenclature of fossil plants, which was suggested by Jefferson Prado. It was confirmed that the name Maria I.A.Dobruskina (1980: 92) is a valid name of a fossil gymnosperm (Peltaspermaceae). In accordance with the Code, the new generic name Hijmania M.D.M.Vianna is proposed as a replacement name. New combinations for the four species assigned by Vianna et al. (2013) to Maria M.D.M.Vianna are here proposed under Hijmania. The new generic name maintains the honorific to Maria Hijman, for her great contribution to the knowledge in Moraceae.